PENGARUH CONTENT MARKETING, E-WOM, DAN PERSEPSI KUALITAS TERHADAP MINAT BELI PRODUK SOMETHINC PADA PENGIKUT AKUN X @SOMETHINC_OFFICIAL - Wenda, Bellty Delincya Evalda; Zulistiani; Sardanto, Rino (Universitas Nusantara PGRI Kediri, 2025)
This study aims to analyze the influence of content marketing, electronic word of mouth (e-WOM), and perceived quality on the purchase intention of Somethinc products on followers of the X account @Somethinc Official. Using a quantitative approach with a survey method to 100 respondents through a purposive sampling technique, the data was analyzed using SPSS 27. The results showed that content marketing and e-WOM had a significant effect on increasing the purchase intention of Somethinc consumers, while the perception of quality did not have a significant effect in the context of marketing through X. This shows that consumers are more influenced by informative content and positive reviews from fellow users in making decisions to purchase local skincare products on social media, compared to the perception of quality factor. The novelty of this study lies in the focus of analyzing the behavior of local skincare consumers through the X platform which is still rarely studied, and emphasizing the importance of utilizing content-based marketing strategies and e-WOM in increasing purchase intention. This study is expected to provide a practical contribution for Somethinc in optimizing digital marketing strategies in order to reach consumers more effectively, while enriching theoretical studies of digital marketing in the local skincare industry in Indonesia.